Pharmacological and Biophysical Characteristics of Picrotoxin-Resistant, δSubunit-Containing GABAA Receptors - Shu, Hong-Jin; Lu, Xinguo; Bracamontes, John; Steinbach, Joe Henry; Zorumski, Charles F.; Mennerick, Steven (Frontiers in Synaptic Neuroscience, 2021)
GABAA receptors (GABAARs) play a crucial role in inhibition in the central nervous system. GABAARs containing the δ subunit mediate tonic inhibition, have distinctive pharmacological properties, and are associated with disorders of the nervous system. To explore this receptor sub-class, we recently developed mice with δ-containing receptors rendered resistant to the common non-competitive antagonist picrotoxin (PTX). Resistance was achieved with a knock in point mutation (T269Y; T6’Y) in the mouse genome. Here we characterize pharmacological and biophysical features of GABAARs containing the mutated subunit to contextualize results from the KI mice. Recombinant receptors containing δ T6’Y plus WT α4 and WT β2 subunits exhibited 3-fold lower EC50 values for GABA but not THIP. GABA EC50 values in native receptors containing the mutated subunit were in the low micromolar range, in contrast with some published results that have suggested nM sensitivity of recombinant receptors. Rectification properties of δ-containing GABAARs were similar to γ2-containing receptors. Receptors containing δ T6’Y had marginally weaker sensitivity to positive allosteric modulators, likely a secondary consequence of differing GABA sensitivity. Overexpression of δT6’Y in neurons resulted in robust PTX-insensitive IPSCs, suggesting that δ-containing receptors are readily recruited by synaptically released GABA. Overall, our results give context to use of δ receptors with the T6’Y mutation to explore the roles of δ-containing receptors in inhibition.